2022
DOI: 10.3390/buildings12040492
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Smartphone-Based Public Participation in Earthquake Structural Response Emergency Monitoring Using a Virtual Experiment and AI

Abstract: Structural health monitoring (SHM) is of great significance for post-earthquake damage assessment. Smartphone-based monitoring techniques provide the possibility to perform crowdsensing for all buildings in urban regions after an earthquake. However, this idea still faces many difficulties and is hard to realize. Fortunately, the development of game engines provides the opportunity for simulating this kind of experiment. The main objective of this study was to use Unity to simulate the whole process when a cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Four studies propose methods : Kitazato et al [ 39 ] propose a method to detect real-time pedestrian flows which is believed to be crucial for disaster evacuation guidance. Li et al [ 40 ] suggest a method to simulate the post-earthquake evacuation and mobile crowdsensing-based monitoring of citizens under instructions from a central authority. Zabota and Kobal [ 41 ] discuss a new methodology for collecting data on past rockfall events through mobile application to enhance the quality of rockfall risk assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies propose methods : Kitazato et al [ 39 ] propose a method to detect real-time pedestrian flows which is believed to be crucial for disaster evacuation guidance. Li et al [ 40 ] suggest a method to simulate the post-earthquake evacuation and mobile crowdsensing-based monitoring of citizens under instructions from a central authority. Zabota and Kobal [ 41 ] discuss a new methodology for collecting data on past rockfall events through mobile application to enhance the quality of rockfall risk assessment.…”
Section: Resultsmentioning
confidence: 99%
“…The data are reported into the app by the crowd, so crowd as reporter can be noted as another sensor used in this work. Li et al [ 40 ] discusses structural health monitoring, i.e., regional building damage assessment, through mobile crowdsensing. An earthquake strike in a city is simulated in ’Unity’ simulation environment where ‘Ground Eye’ acts as the city brain to coordinate emergency response and assign tasks to citizens to collect data on damage assessment.…”
Section: Resultsmentioning
confidence: 99%
“…The evacuation speed of constructors is directly affected by the working faces with an emergency situation in the construction site [12,26,29]. VR equipment and the BIM model are considered valuable in most safety evacuation studies with easier alternatives to experiments [8,22,29,30,[39][40][41][42][43], and the author has confirmed that experiments with VR equipment and the BIM model are reasonable proxies of the evacuee's performance under emergency scenarios in the existing research [41]. The evacuation speed of constructors is tested by VR equipment and the frame-core tube building BIM model with twenty constructors, and the test is shown in Figure 4.…”
Section: Survey Research Of Construction Sitementioning
confidence: 99%
“…To minimize the high number of constructors' injuries and fatalities, numerous practices that range from behavioral to engineering safety approaches have been implemented in construction over the last few decades. High-risk factors in construction sites and optimal construction layout for evacuating are becoming emerging trends [29][30][31]. Constructors are a special group with a high-risk occupation, and their characteristics affecting a safety evacuation are worth studying in detail to improve safety performance in the construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [28] proposed a new visual cable force measurement method based on smartphone cameras, and preliminarily verified its feasibility and practicability through cable model tests. Li et al [29] provided the possibility of crowd perception of all buildings in urban areas after the earthquake with smartphone-based monitoring technology. Ozer et al [30] introduced the concept of smartphone structural health monitoring and constructed a hybrid structure vibration response measurement framework by using multi-sensor smartphone functions.…”
Section: Introductionmentioning
confidence: 99%